Prevalence of gynaecological morbidities and their association with sociodemographic factors among women aged 18-49 years attending outpatient clinic of an outreach center of a medical college in Delhi - Sarah A. Habib; Sushovan Roy; Aqsa Shaikh (Journal of Family Medicine and Primary Care)
Background: Gynecological issues are a major cause of morbidity and mortality worldwide, with women in developing nations bearing the greatest disease burden. It significantly affects women’s lives as well as that of their children and families. Not many studies have been done on Gynecological Morbidity in a facility-based setting in New Delhi, this study was conducted to measure the prevalence of Gynecological Morbidity and their associated Sociodemographic Factors in women aged 18–49 years. Objectives: 1. To estimate the prevalence of gynecological morbidities in women aged 18–49 years attending RHTC of a Medical College in South-East Delhi. 2. To determine the sociodemographic factors associated with gynecological morbidities in the study group. Methods: A cross-sectional study was conducted in the health center of a medical college in Delhi among women 18–49 years of age. 400 participants were included in the study through systematic random sampling. A pretested, validated questionnaire was used for data collection using Epicollect-5 software. SPSS version, 26 (SPSS Inc., USA) software was used for data analysis. The Chi-square test was used to measure the association and a P value of <0.05 at a 95% confidence interval was taken as significant. Results: A total of 61.2% of women reported at least one gynecological morbidity with the majority having dysmenorrhea (61.3%), followed by irregular menses (36.1%) and infertility (36.1%). Among the age group of 18–24 years, those who were never married, and among sexually inactive women, dysmenorrhea was found more commonly (P < 0.05). Irregular menses was reported mostly by women in age group 25–30 years, never married, those who studied till middle school and lower socioeconomic class. Infertility, dyspareunia, and dysuria also showed significant association with various sociodemographic characteristics. Conclusion: A high prevalence of gynecological morbidities was seen in the women attending the outpatient clinic of a health center. Majorly, dysmenorrhea, irregular menstruation, and infertility were seen.